2022
DOI: 10.3390/en15165882
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Biomass and Biochar of Maritime Pine as a Porous Medium for Water Retention in Soils

Abstract: Pinewood biomass in Portugal can be considered a major source of biochar for soil physical, chemical, and biological edaphic amendment. This work intended to evaluate the aptitude of lab produced biochar for upgrading soil moisture dynamics’ relationships considering mixtures of biochar with silica-based sand. The methodology used focused on the carbonization of pine biomass with inert atmosphere at 300 °C, 400 °C, 500 °C and 600 °C, followed by a chemical proximate and thermogravimetric analysis, scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…As pore size was found between 2 to 50 nm (8.35 nm), so pores of biochar of weed C. gigantea is classi ed as mesoporous (as per IUPAC classi cation). This is attributed to the volatilization of the organic compound (Fu et al 2012, Sheau et al 2014, Santos et al 2022. By examining the structural appearance of the SEM micrograph, it is found that irregular elliptical pores are arranged in cross-linked forms over the surface (Fig.…”
Section: Bet and Sem/edx Of Biocharmentioning
confidence: 95%
See 1 more Smart Citation
“…As pore size was found between 2 to 50 nm (8.35 nm), so pores of biochar of weed C. gigantea is classi ed as mesoporous (as per IUPAC classi cation). This is attributed to the volatilization of the organic compound (Fu et al 2012, Sheau et al 2014, Santos et al 2022. By examining the structural appearance of the SEM micrograph, it is found that irregular elliptical pores are arranged in cross-linked forms over the surface (Fig.…”
Section: Bet and Sem/edx Of Biocharmentioning
confidence: 95%
“…Scanning electron microscopy (SEM) and electron dispersive X-ray analysis (EDX) techniques are used to examine the structure of pores on surface and distribution of minerals in the biochar, respectively. The ligno-cellulosic raw material have brous and cellular structures, such as trachieds, which form the carbon matter after thermal degradation and with increase in temperature the surface morphology of the biochars sophistically changes with the gradual opening of pores on the surface (Liang et al 2016, Santos et al 2022. Further mores pores are also generated due to the decomposing and melting of chemical bonds and structure of raw biomass (Fu et al 2009, Sheau et al, 2014).…”
Section: Bet and Sem/edx Of Biocharmentioning
confidence: 99%
“…Taking into consideration the reduction of the swelling degrees at high reactant concentrations, we assume that the increase of the specific surface area of the hydrogel samples is the determinant factor for the samples, which presented smaller pore sizes and higher swelling degrees [ 48 ]. Large specific surfaces of small pores could allow the retention of more fluid due to the higher contact surface between the material and the fluid [ 49 , 50 ]. Certainly, the fluid uptake can be governed by the chemical structure of the samples, their morphology, meaning the porosity together with the specific surface of the pores, or more likely by an input of each.…”
Section: Resultsmentioning
confidence: 99%
“…WHC is controlled mainly by the soil's pore number/distribution and surface area [57]. Biochar has been shown to effectively retain water in its pores due to its high porosity and irregular shape [58]. Decreasing biochar particle size from the macro-to micro-range can result in more available sites for water adsorption and higher WHC [58].…”
Section: Digestate Qualitymentioning
confidence: 99%
“…Biochar has been shown to effectively retain water in its pores due to its high porosity and irregular shape [58]. Decreasing biochar particle size from the macro-to micro-range can result in more available sites for water adsorption and higher WHC [58]. Previous studies showed that biochar can adsorb 10 times its weight in water and increase soil WHC up to 30% [58].…”
Section: Digestate Qualitymentioning
confidence: 99%